Protection of old forges in Sułkowice – symbol of the local crafts-manship - Zin, Barbara (Budownictwo i Architektura / Civil and Architectural Engineering, 2015)
Wooden structures linked to agriculture are disappearing from the image of the Polish countryside, villages and small towns at the beginning of the 21st century. It is worthy to start the discussion on the fate of desolate, deteriorating forges, sawmills, carpentries, or water mills which are relics of the traditional technology. Sułkowice, a small town in the Małopolskie voivodeship, has been known for ages as a prominent centre of blacksmiths and their craft. Even today one feels the specific character of the landscape; in the mid-19th century circa 1000 blacksmiths worked there. Tradition lived until the times after the Second World War – when artisans in Sułkowice forged, among others, artful fittings for the MS ‘Batory’ [famed Polish liner]. Inventories, surveys and measurements of old forges, elaborated by the authoress within the framework of the research grant “Image of villages and small towns in Poland of the last decade of the 20th century” (led by Prof. Wiktor Zin) led to gathering of the documentation of circa 20 structures hailing from the close of the 19th century. After 20 years that elapsed since the research there are only a few left, and their days are numbered. Local Programme of Revitalisation of the Town from the year 2007 which is a strategic plan for enterprises aiming at amelioration of the area, does not mention the protection of the last witnesses of the local crafts’s tradition. Whereby the activisation of the local community, deriving from the tradition of the place, should be the aim of such a programme. Thus maybe there should be reconstruction and later ‘cyclical rebuilding’ of the structures which have no chance to exist with their primary function? “Old-new” wooden structures shall be a reminder of the blacksmiths’ tradition.